2022
DOI: 10.1021/acsinfecdis.1c00474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phenol-Substituted Diphyllin Derivatives as Selective Antagonists for Ebola Virus Entry

Abstract: Ebola virus (EBOV) is an aggressive filoviral pathogen that can induce severe hemorrhagic fever in humans with up to 90% fatality rate. To date, there are no clinically effective small-molecule drugs for postexposure therapies to treat filoviral infections. EBOV cellular entry and infection involve uptake via macropinocytosis, navigation through the endocytic pathway, and pH-dependent escape into the cytoplasm. We report the inhibition of EBOV cell entry via selective inhibition of vacuolar (V)-ATPase by a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
(120 reference statements)
0
1
0
Order By: Relevance
“…The mechanism research revealed that they modulated the endosomal pH. These results were consistent with the fact that diphyllin is a selective pH-dependent viral entry block in late endosomes [60]. In 2022, Michal Štefánik et al reported that diphyllin and diphyllinosides (Cleistanthin B 8) displayed broad-spectrum antiviral activities against multiple enveloped RNA and DNA viruses by blocking the replication of these viruses.…”
Section: Anti-virus Activitymentioning
confidence: 53%
“…The mechanism research revealed that they modulated the endosomal pH. These results were consistent with the fact that diphyllin is a selective pH-dependent viral entry block in late endosomes [60]. In 2022, Michal Štefánik et al reported that diphyllin and diphyllinosides (Cleistanthin B 8) displayed broad-spectrum antiviral activities against multiple enveloped RNA and DNA viruses by blocking the replication of these viruses.…”
Section: Anti-virus Activitymentioning
confidence: 53%
“…S10 – S13 ). Lysosome-Associated Membrane Protein 1 (LAMP1) was used as a lysosomal marker 42 , RAB5 as an early endosome marker 43 , and clathrin (CLTC) as a marker for coated vesicles and coated pits involved in endocytosis 43 . In secretory stage ameloblasts, ACP4 immunostaining was restricted largely to the Tomes’ process, the specialized secretory organ comprising the distal membrane of secretory ameloblasts.…”
Section: Resultsmentioning
confidence: 99%